Determinants of public willingness to fund urban tree planting in Lagos metropolis, Nigeria (2011)
This study examined the public willingness to finance urban tree planting in Lagos metropolis. Nigeria and the associated factors capable of influencing the willingness. Descriptive statistics and Tobit model at 5% level of significance were used to analyse data obtained from multi-stage randomlv sampled 873 Lagos metropolitan residents. The results revealed that 84% of the respondents were willing to contribute funds to Urban Tree Planting (UTP) in Lagos metropolis with N1000 being the modal value of what they were willing to contribute annually. Furthermore, 78.92% of the respondents expressed interest in tree planting. 81.67% were living or working in a green environment and 91.18% were aware of environmental issues. Also 18.10'%. 22.45%, 23.25% and 30.24% had made use of Nature Park, Botanical Gardens. Zoological Gardens, and Street Trees respectively. while 20.73%, 12.83%, and 12.83% had made use of urban forest for religious purposes. provision of medicinal plants and solitude respectively. Fourteen of the 25 regressors were found to significantly affect both the willingness to fund and the prospective contributory amount for UTP in Lagos metropolis. The large proportion of the respondents who expressed interest in tree planting and were willing to contribute funds to urban tree planting portends a great potential for community funding or urban tree planting in Lagos metropolis.